2014
DOI: 10.18632/oncotarget.2237
|View full text |Cite
|
Sign up to set email alerts
|

A 5-gene classifier from the carcinoma-associated fibroblast transcriptomic profile and clinical outcome in colorectal cancer

Abstract: Based on 108 differentially expressed genes between carcinoma-associated fibroblasts (CAFs) and paired normal colonic fibroblasts we recently reported, a 5-gene classifier for relapse prediction in Stage II/III colorectal cancer (CRC) was developed. Its predictive value was validated in datasets GSE17538, GSE33113 and GSE14095. An additional validation was performed in a metacohort (n=317) and 142 CRC patients by means of RT-PCR. The 5-gene classifier was significantly associated with increased relapse risk an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 47 publications
(44 reference statements)
1
27
0
1
Order By: Relevance
“…Data presented here, in addition to these referenced studies (12,(18)(19)(20), highlight that expression of a small number of genes in fibroblasts associated with the tumor, in combination with the overall fibroblast content, is sufficient to identify poor prognostic patients in stage II colorectal cancer. It is unsurprising therefore that the prognostic value of the CMS4 subtype, and indeed other current transcriptional-based prognostic classifiers, is highly dependent on stromal-derived gene signatures and that our 30-gene Stromal Classifier also identifies a group of patients with a worse prognosis.…”
Section: Discussionmentioning
confidence: 71%
“…Data presented here, in addition to these referenced studies (12,(18)(19)(20), highlight that expression of a small number of genes in fibroblasts associated with the tumor, in combination with the overall fibroblast content, is sufficient to identify poor prognostic patients in stage II colorectal cancer. It is unsurprising therefore that the prognostic value of the CMS4 subtype, and indeed other current transcriptional-based prognostic classifiers, is highly dependent on stromal-derived gene signatures and that our 30-gene Stromal Classifier also identifies a group of patients with a worse prognosis.…”
Section: Discussionmentioning
confidence: 71%
“…In addition to the quantity of tumor stroma, its composition may be an important determinant of cancer behavior. For example, the presence of cancer-associated fibroblasts (CAFs) effectively predicts tumor recurrence in CRC patients [102]. Recently, an immune-histochemical score based on the expression of two proteins specific for CAFs has additionally been able to predict the response to neoadjuvant treatment in rectal cancer [103].…”
Section: Stromal Densitymentioning
confidence: 99%
“…Furthermore, CAFs secrete ECM and proteases including cathepsins, plasminogen activators, and matrix metalloproteases, consequently induce EMT and increase invasive growth of CRC cells (Tommelein et al, ). It has been shown that the 5‐gene signature derived from CAF (CCL11, AMIGO2, ULBP2, SLC7A2, and PDLIM3) predicts risk of recurrence in stage II patients precisely compared to conventional clinicopathological criteria alone (Berdiel‐Acer et al, ). Interestingly, CAFs amplify the membrane‐bound serine protease, fibroblast activation protein (FAP) which is not detectable in normal fibroblasts.…”
Section: The Tissue Microenvironment In Colorectal Cancermentioning
confidence: 99%
“…patients precisely compared to conventional clinicopathological criteria alone(Berdiel-Acer et al, 2014). Interestingly, CAFs amplify the membrane-bound serine protease, fibroblast activation protein (FAP) which is not detectable in normal fibroblasts.…”
mentioning
confidence: 99%